Employee Engagement Pendeta GMIT dan Dampaknya bagi Spiritualitas Pelayanan Pendeta di Jemaat-Jemaat Se-Klasis Kupang Barat - Koli, Endang Damaris; De Haan, Arly Elizabeth Maria; Taneo, Rolin Ferdilianto Sandelgus (JURNAL LUXNOS, 2024)
Abstract: The Evangelical Christian Church in Timor has two ecclesiastical positions, namely ministry positions and organizational positions. The pastor is a church official who carries these two positions. As servants of Christ, pastors together with other church officials are given the task of translating the vision of the Kingdom of God and leading the implementation of the mission that Christ has entrusted to their church. In the GMIT Code, pastors are also referred to as employees. As employees, pastors are Expected to have involvement, motivation and dedication or employee engagement as a commitment to Christ through the church. With employee engagement, it is hoped that the spirituality of service will be maintained. This research aims to find out how employee engagement operates in the duties of GMIT pastors, especially in the West Kupang classist area and whether this influences the spirituality of their ministry. This research uses library study and field research methods. The results obtained in interviews with resource persons were then elaborated with theories related to the field study material. The results of the research show that GMIT pastors in the West Kupang area still have commitment as organizational officials and maintain spirituality as ministry officials.